To determine the pattern and severity of cardiac valves involvement in children with rheumatic heart disease - Goel, Manjusha; Agrawal, Amit; Kumar, Pradip; Dwivedi, Rashmi; Yadav, B S (Indian Journal of Child Health, 2016)
Background: Rheumatic heart disease (RHD) is the most common cardiovascular disease in children and young adults and is a major public health problem in developing world. Objectives: To determine the relative frequency and severity of the cardiac valve lesions in children, diagnosed as RHD. Materials and Methods: This prospective observational study was conducted from January 2013 to December 2014 in the Department of Pediatrics and Cardiology of teaching institution. Children less than 15 years of age fulfilling the selection criteria of RHD were evaluated by transthoracic echocardiography for pattern and degree of valvular involvement, according to the American Heart Association/American College of Cardiology guidelines. Results: A total of 45 patients (23 males and 22 females) were studied. The most common age group was 10-12 years, 91.11% cases belonged to lower socio-economic class. The most common lesion was mitral regurgitation (MR) (91.11%) with female predominance (51.22%) followed by atrial regurgitation (AR) (51.11%) with female (56.53%) predominance, mitral stenosis (MS) (26.66%) with male (58.33%) predominance, and tricuspid regurgitation (24.44%) with female (63.64%) predominance. Out of 45 cases of RHD, 29 cases (64.44%) had combined valvular lesions, out of which 14 cases (48.28%) had both MR and AR. Conclusion: RHD is still a common problem in our country. In our study, the most of the patients had combined valvular lesions. The predominant lesion was MR followed by aortic regurgitation and MS. Regurgitant lesions were seen predominantly in females while stenotic lesions were seen in males. Echocardiography should be done routinely for patients with RHD, focusing on younger population, to facilitate diagnosis and definitive treatment before complications set in.